2007
DOI: 10.4321/s1886-36552007000100008
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacovigilance study in the department of medicine of a university teaching hospital

Abstract: promotion of rational prescribing and drug use in the hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 14 publications
6
17
0
Order By: Relevance
“…The demographic details of our study showed a female gender predominance over males for ADRs, (F-54%, M-46%) which was similar to that which was found in other studies which have been reported in the literature [17,18], though on the other hand, some studies have been published, where males were implicated more as compared to females [19,20].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The demographic details of our study showed a female gender predominance over males for ADRs, (F-54%, M-46%) which was similar to that which was found in other studies which have been reported in the literature [17,18], though on the other hand, some studies have been published, where males were implicated more as compared to females [19,20].…”
Section: Discussionsupporting
confidence: 89%
“…This was at par with the findings of a study which was done by Sharma et al, [20] Not many studies took this point into consideration as one of the drug characteristics in ADR monitoring. The more common intake of oral drugs as compared to parenteral ones could be one of the reasons for this particular finding.…”
Section: Discussionsupporting
confidence: 69%
“…The demographic details of our study population showed female gender predominance over males, which was similar to that reported in other studies found in the literature [10,11,14-18]. This might be due to higher emotion quotient in females, which makes them more sensitive to the pharmacological actions of medicines, thus enhancing the probability of ADRs.…”
Section: Discussionsupporting
confidence: 88%
“…As expected, combination therapy was associated with higher number of ADRs as compared to monotherapy. Amlodipine and atenolol combination therapy leads to greater risk of ADRs than the monotherapy as reported earlier[61819]. In this study we found that CCBs were the commonest group of drugs prescribed, though beta-blockers and ACE inhibitors were associated with higher incidences of ADRs.…”
supporting
confidence: 77%